Managing information (Buckingham : Open University Press, 2000)
The international framework of information policies. Information: the UK national scene. Management of information in further and higher education. Information strategies. The administrator and information. Managing information in research. Applying technology to learning: making links between theory and practice. Intellectual property rights. Towards the electronic library. Information management: future perfect or past imperfect?
Keywords: Management; Administration; Data processing; Information resources management -- Great Britain; Universities and colleges -- Great Britain -- Administration -- Data processing